Effects of conservation tillage on total and aggregated soil organic carbon in the Andes - Quintero, Marcela; Comerford, N.B. (Scientific Research Publishing, Inc., 2013)
Many Andisols of the Andes have been disturbed by traditional potato-based rotation agriculture disrupting soil structure, water retention capacity and organic matter content.This study was undertaken to investigate the contribution of conservation farming technology or reduced tillage in potato-based rotations in the Colombian Andes in order to rehabilitate total and aggregated soil organic C in disturbed organic matter-rich Andisols.Soils were sampled from farms with 7-year of reduced tillage and farms with conventional farming practices.Ultrasound energy was applied to samples to disrupt aggregation and total soil C was determined in order to investigate the amount of carbon held inside the aggregates of different soil size classes.Results indicated that reduced tillage in potato-based crop rotations increased the soil C concentration and average C content in the whole profile (≈117 cm depth) by 50 and 33% (1636 t C ha -1 vs. 1224 t C ha -1 ), respectively, as compared to conventional farming practices.Carbon content increased 177% in the subsoil (A2 horizon, 78 -117 cm depth, from 215 to 596 t•ha -1 ), although most of the soil C was in the A1 horizon (between 0 -78 cm average thickness, 1097 t•ha -1 ).These increases show that reduced tillage enhances C stores in Andisols which are already high in organic matter.In addition, C in aggregates represented more than 80% of the total organic matter and it was positively affected by conservation practices.The C increase was preferential in the smaller macroaggregates (<2 mm).The aggregate dispersion energy curves further suggested that C increase was occurring in microaggregates within the smaller macroaggregate fraction.Data suggested that smaller macroaggregates can be used in these soils to evaluate the influence of field management practices on soil C sequestration.